A Study of Brachial Plexus Sheath and Dye Spread Through the Sheath in Single- and Multi-Directional Injections in Cadaver - Subhramoy Chaudhury; Anasuya Ghosh (Wolters Kluwer Medknow Publications, 2021)
Background: The in-depth understanding of the anatomy of brachial plexus (BP) sheath is very important for the successful application of BP block. The flow dynamics of injectable anesthetic might vary depending on the site and mode of injection. The objectives of this study were to explore and document the detailed anatomy of BP sheath and to compare the dye spread by injections given in single direction and multi-directional approaches in formalin-fixed cadavers. Materials and Methods: This study is a descriptive, observational, and cross-sectional study based on findings on cadaver dissection and injecting dye in cadavers. Twenty-four sides of 12 well-embalmed cadavers were utilized for injecting dye solution into the intact brachial sheath by single-direction and multi-direction injection approaches at the axillary level. All the cadavers were dissected to compare the spread of dye in two approaches. In addition, one more cadaver was utilized for a detailed dissection of the infraclavicular part of BP sheath and its contents without injecting dye. Microsoft Excel software was used for statistical analysis. Results: We observed BP sheath was a fibrous connective tissue sheath-containing multiple neurovascular structures, all of which had individual delicate connective tissue wrapping around them. More uniform dye spread was observed in multi-direction approaches and the musculocutaneous nerve was stained more frequently in multi-direction approach. Conclusions: The presence of delicate porous connective tissue wrapping gives a tunnel-like appearance of the infraclavicular part of BP sheath. Multi-directional injections resulted in dye staining of the larger area involving more structures than single-direction injections.